PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN MAMUJU UTARA - Idamayanti, Andi (Katalogis, 2016)
The aim of this study; (1) to determine the influence of achievement needs (need for acbievement), power needs (need for power), and the relationship needs (need for affiliation) simultaneously (together) against the employee's performance Regional Development Planning Agency of North Mamuju regency; (2) to determine the power needs (need for power) partially (people) to the employee's performance Regional Development Planning Agency of North Mamuju regency; (3) to determine the effect relationship needs (need for affiliation) partially (people) to the employee's performance Regional Development Planning Agency of North Mamuju regency; (4) to determine the influence of achievement needs (need for acbievement) partially (people) to the employee's performance Regional Development Planning Agency of North Mamuju regency. This type of research is quantitative and descriptive. The study population is employees of the Regional Development Planning Agency of North Mamuju regency totaling 31 respondents. Sampling techniques using the census, so that the entire population sampled, as well as data analysis techniques using multiple linear regression. The results showed; (1) The need for achievement (need for acbievement), power needs (need for power), and the needs of the relationship (need for affiliation) simultaneously (together) affect the employee's performance Regional Development Planning Board Mamuju Utara, with effect of 43 , 9% and the level of relationship